(untitled) (Journal of the Bangladesh Agricultural University, 2016)
Groundwater samples of shallow and deep tubewells were collected from the different villages of Bhaluka upazilla in Bangladesh to assess their quality status for drinking, irrigation and livestock consumption. Different parameters of waters were determined to evaluate the quality. All the waters were alkaline in nature and electrical conductivity classified the samples as good for irrigation, while the TDS categorized the samples highest desirable limit for drinking and fresh water for irrigation and were suitable for drinking, irrigation and livestock consumption. Chloride content rated 2 samples unsuitable for livestock consumption. The concentrations of Zn were within safe limit, but Fe and Mn contents rated almost all the samples unsuitable for drinking and livestock consumption.With respect to Cu concentration, 8 samples were found unsuitable for long- term irrigation on all types of soils. Out of 17 samples, 12 samples classified as excellent, 4 as good and 1 as doubtful for irrigation due to different level of B. Ca, Mg, Na, K and P quantities of all the samples were within safe limit. SAR and EC rated all the samples as medium salinity and low alkalinity class and hardness of most of the waters were hard water class for irrigation. J. Bangladesh Agril. Univ. 12(2): 313-319, December 2014